The Role of Leader in coaching through Neuro-Linguistic Programming approach - Siti Nurhayati Arista; Irmawan Rahyadi (Budapest International Research and Critics University, 2022)
Neuro-Linguistic Programming, coined by Bandler and Grinder, broadly denotes the view that a person is a whole mind-body system with patterned connections between an internal experience calls neuro, language for linguistic, and behavior for programming. NLP has been defined in various ways, often in its promotional literature as the art of communication excellence” or “the study of the structure of subjective experience”. Data obtained from the International Coach Federation (ICF), a professional coach agency with the largest members in the world, proves that every year the number of professional coaches is always increasing. In 2019, number of professional coaches was 35,594 members until July 2020, increased to 41,537 members in 147 countries and territories. This proves that coaching is increasingly popular and in demand for various needs. This article discusses how the implementation of coaching through Neuro-Linguistic Programming for Leader to achieve company goals because many companies in Indonesia have implemented NLP-based training tailored to the required context. The qualitative method is done by conducting interviews with respondents namely Managers, Supervisors and Staff. As a result, the implementation of coaching through the Leader has been implemented, but is still followed by training carried out to maintain productivity, achieve goals, and motivate employees to stay focused on the targets set by the company.